Private Vehicle Roadworthiness Inspection – Towards ELV Realization - Solah, M.S.; Hamzah, A.; Ariffin, A.H.; Abdul Khalid, M.S.; Salleh, A.S.; Rahim, S.A.S.M.; Abu Kassim, K.A. (Journal of the Society of Automotive Engineers Malaysia, 2021)
Being one of the most critical sectors worldwide, the rapid increase of automobility has necessitated effective management of End-of- Life Vehicles (ELVs). However, in Malaysia, an ELV policy and initiative is absent from the country’s automotive ecosystem which resulted in a proliferation of aged and unsafe vehicles; thus potentially increasing the chance of occupant injury in a crash. The government had already mooted an ELV policy but due to public outcry, the proposed plan for the scrapping of aged vehicles was postponed. This paper aims to provide an overview of a potential private vehicle inspection to be introduced and also the challenges facing the government towards the implementation of the ELV directive in Malaysia. It is believed that the results presented in this paper will be useful to academics, government officials, and researchers to establish strategies for ELV policy in Malaysia effectively via a vehicle roadworthiness inspection.